2020
DOI: 10.3390/polym12051184
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based MEMS Electromagnetic Actuator for Biomedical Application: A Review

Abstract: In this study, we present a comprehensive review of polymer-based microelectromechanical systems (MEMS) electromagnetic (EM) actuators and their implementation in the biomedical engineering field. The purpose of this review is to provide a comprehensive summary on the latest development of electromagnetically driven microactuators for biomedical application that is focused on the movable structure development made of polymers. The discussion does not only focus on the polymeric material part itself, but also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 113 publications
0
32
0
Order By: Relevance
“…For instance, The wearable electromagnetic actuator researched by Fabrizio pace and his co-workers [140] belongs to this type of structure (Figure 22a). The common magnetic materials that have been reported in the literatures include nickel-plated neodymium and NdFeB magnet and the Flexible materials include PMMA, parylene, polyimide and PDMS elastomer [141].…”
Section: Structurementioning
confidence: 99%
“…For instance, The wearable electromagnetic actuator researched by Fabrizio pace and his co-workers [140] belongs to this type of structure (Figure 22a). The common magnetic materials that have been reported in the literatures include nickel-plated neodymium and NdFeB magnet and the Flexible materials include PMMA, parylene, polyimide and PDMS elastomer [141].…”
Section: Structurementioning
confidence: 99%
“…Some other studies had reported the research progress on MEMS energy harvesting utilizing piezoelectric ( Shi et al., 2016 ); electrostatic ( Oxaal et al., 2016 ) and multi-frequency mechanical vibration-based electromagnetic energy conversion ( Liu et al., 2013 ). Meanwhile, the investigations on the functional material, such as polymer composites applied to an electromagnetic actuator ( Yunas et al., 2020b ) and the expansion of the MEMS energy harvester into the internet of things system (IoT) ( Duque et al., 2019 ; Iannacci, 2019 ) have enriched the literature significantly in the field of MEMS energy harvester.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these emerging requirements, recent research activities have been directed towards improving BMS by using the Internet of Things (IoT) [4]- [8] and by creating a new paradigm, the Internet of Medical Things (IoMT) [1], [9]. These IoMT solutions are mainly based on wearable and implantable biomedical measurement devices [12] using different sensors, such as tactile [13], silicon [14], polymer [15] and opticalbased sensors [16], [17] or sensors already integrated into commonly used devices, such as smartphones [3], [18]- [23].…”
Section: Introductionmentioning
confidence: 99%